The impact of lifestyle, age, and sex on systemic and airway inflammation and oxidative stress - Kurti, Stephanie P. (Kansas State University, 2017)
The overall aim of this dissertation was to determine the impact of lifestyle (i.e. habitual and acute physical activity and diet), age, and sex on systemic and airway inflammation and oxidative stress. In study 1 (Chapter 2) we examined the impact of habitual physical activity level on the post-prandial airway inflammatory response following an acute bout of moderate intensity exercise. Results indicated that the mean exhaled nitric oxide (eNO; marker of airway inflammation) response increased for all groups at two hours post high-fat meal (HFM) (~6%) and returned to baseline by four hours post-HFM. However, there was a varying eNO response from baseline to four hours in the group that exercised in the post-prandial period compared to the group that remained sedentary. These findings suggest airway inflammation occurs after a HFM when exercise is performed in the post-prandial period, regardless of habitual physical activity level. In study 2 (Chapter 3) we investigated the post-prandial oxidative stress response to meals of varying calories and fat. Specifically, we assessed the post-prandial airway and systemic 8-isoprostane (a marker of oxidative stress) responses to meals with moderate-fat (8.5 kcal/kg of bodyweight) and high-fat content (17 kcal/kg of bodyweight) from baseline to six hours post-meal in a randomized crossover design. This study revealed that systemic 8-isoprostane increased from baseline to six hours post-meal (38.3%), but there was no difference between the moderate-fat meal (MFM) and HFM conditions. There were no changes in airway 8-isoprostane from baseline to six hours post-MFM or HFM, or between the MFM and HFM conditions. Lastly, in study 3 (Chapter 4), we were interested in examining 8-isoprostane responses in older adults, since 8-isoprostane has been reported to increase with age. Previous research also suggests that older women (OW) and older men (OM) have differences with regard to prevalence and severity of late-onset asthma. In this study, we sought to determine whether the airway 8-isoprostane response to a strenuous bout of exercise was different in OW compared to OM. A secondary aim was to determine whether post-exercise 8-isoprostane generation was correlated with decrements in lung function. Our results showed that the generation of 8-isoprostane from pre- to post-exercise increased ~74±77% in OW and decreased ~12±50% in OM. The decrease in 8-isoprostane generation was not correlated with improvements in lung function from pre- to post-exercise. These findings collectively contribute to the literature by enhancing our understanding of the impact of lifestyle factors, age and sex on modifying and potentially mitigating the risk of developing chronic diseases.
Keywords: Acute and chronic exercise; Airway inflammation; 8-isoprostane; Older adult; High-fat mealPulmonary physiology